Hybrid additive manufacturing of precision engineered ceramic components. Issue 6 (30th July 2019) - Hinton, Jack; Basu, Dejan; Mirgkizoudi, Maria; Flynn, David; Harris, Russell; Kay, Robert
Abstract : Purpose: The purpose of this paper is to develop a hybrid additive/subtractive manufacturing platform for the production of high density ceramic components. Design/methodology/approach: Fabrication of near-net shape components is achieved using 96 per cent Al3O2 ceramic paste extrusion and a planarizing machining operations. Sacrificial polymer support can be used to aid the creation of overhanging or internal features. Post-processing using a variety of machining operations improves tolerances and fidelity between the component and CAD model while reducing defects. Findings: This resultant three-dimensional monolithic ceramic components demonstrated post sintering tolerances of ±100 µ m, surface roughness's of ∼1 µ m Ra, densities in excess of 99.7 per cent and three-point bending strength of 221 MPa. Originality/value: This method represents a novel approach for the digital fabrication of ceramic components, which provides improved manufacturing tolerances, part quality and capability over existing additive manufacturing approaches.